PENGARUH KESELAMATAN - KESEHATAN KERJA (K3) DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT GRIYA SUMBER MANDIRI SAWANGAN DEPOK - Fadilah Wulandari; Bambang Sutarto (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of occupational health safety and the physical work environment on employee performance at PT Griya Sumber Mandiri Sawangan Depok. This research uses quantitative methods. The data was collected from 75 respondents by questionnaires and the varables are. Occupational health safety (X1) and physical work environment (X2), Employee Performance (Y). Data analysis includes validity, reliability, classical assumptions, regression, correlation coefficient, determination coefficient, hypothesis tests. The results of these research show that there is a significant influence between occupational health safety on employee performance, with a coefficient of determination value of 55.7%, hypothesis test t test > t table (9.574 > 1.993). The physical work environment has a significant effect on employee performance with a determination value of 66.1%, the results of the hypothesis test obtained t test > t table (11.942 > 1.993). Simultaneously, occupational health safety and physical work environment have a significant effect on employee performance with a Y regression of 6.437 + 0.313X1 + 0.553X2. The coefficient of determination value was 68.8%, while the remaining 31.2% was caused by other factors not researched by the author. Hypothesis testing obtained calculated f test > f table (79.510 > 2.730).